Advanced Education in the Information Society - Knyaginin, Vladimir Nikolaevich; Meshkov, Nikolay Alekseevich; Utolin, Konstantin Vladimirovich (International Review of Management and Marketing, 2016)
The sustainable civilizational development of the society is a necessary condition for ensuring a high level and quality of life of people, their reliable social security. The basis of the strategy of sustainable development of the society is the advanced training. Realization of the concept of advanced training involves the formation of the ability of the education system to "foresee" its future and make decisions about its actions in the present in accordance with this foresight. In the conditions of Russia’s moving towards the information society, new possibilities open up of innovative development of domestic education, improvement of efficiency of the educational process. The article discusses the prospects of innovative development of the Russian education on the basis of realization of the opportunities offered by the information society. A methodology is formulated of the management of innovative development of education in the conditions of information society. A concept is put forward and substantiates of the next-generation intelligent system of management of innovative development of the Russian education, which is capable of advanced training of specialists with professional skills and abilities that will allow them to work in those areas of knowledge and competencies that will only appear by the time of their graduation. Building of a next-generation intelligent system of management of innovative development of the Russian education presupposes implementation of the mechanism of synthesis of the management objective, the construction of a dynamic expert system, ensuring the integration of the system of forecasting/planning in the education sector with a system of forecasting in the area of science and technology and integrated forecasting of socio-economic development of the country, the use of participatory approach to planning, the use for the management of educational development of intelligent control technologies including or based on P.K. Anokhin’s theory of functional systems. Keywords: advanced education, information society, Blue Ocean Strategy, participative planning JEL Classifications: I21; I25; I28; O33